Corporate Social Responsibility of Publicly-Owned Banks is Also a Moderating Factor That Affects Their Returns - Farahillah, Cholidatu Efafa; Sumastuti, Efriyani; Kurniawan, Bayu (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study investigates the impact of profitability, measured by return on assets (ROA) and return on equity (ROE), on a company's value, and explores the moderating role of corporate social responsibility (CSR) in this relationship. Methodology: The research focuses on state-owned banks listed in Indonesia from 2013 to 2022, using data from their financial statements. A saturated sample of 160 quarters across 4 companies was analyzed using Partial Least Square (PLS) statistical methods. Results and Findings: The results indicate that both ROA and ROE positively influence company value. CSR can either strengthen or weaken this relationship, depending on the specific profitability measure. Novelty and Originality: This study provides new insights into how CSR interacts with different profitability measures to affect company value, highlighting the nuanced role of CSR in financial performance. Conclusions: Profitability positively impacts company value, with CSR serving as a significant moderator. The effect of CSR varies based on the profitability measure used. Type of Paper: Research Article.